Performance of Crossbred Goat Kids (Khari × Jamunapari) Fed with Rice Polish and Maize Flour Supplemented with Probiotics and Enzymes in Tanahun District - Barsila, Shanker Raj; Wagle, Saroj; Chetri, Dipesh; Shah, Ramashish (Journal of Agriculture and Forestry University, 2025)
An experiment was conducted on 16 crossbred goat kids (Khari × Jamunapari) aged approximately 3-4 months under farmer-managed conditions in Myagde-3, Tanahun, Nepal, from November 15, 2019, to February 15, 2020. The aim of this study was to determine the effects of feeding on crossbred goat kids (Khari × Jamunapari) fed rice polish and maize flour supplemented with probiotics and enzymes. The animals were assigned to a randomized complete block design (RCBD) on the basis of body weight with 4 treatments and were replicated 4 times. The treatment combinations included fodder only (T1), fodder + rice polish + probiotics + enzymes (T2), fodder + maize flour + probiotics + enzymes (T3), and fodder + rice polish + maize flour + probiotics + enzymes (T4). The parameters studied included proximate nutrient analysis of the feed ingredients, feed consumption, the feed conversion ratio, growth parameters (body length, wither height, heart girth and neck girth) and economic analysis. Body weight gain was recorded at fortnightly intervals, and body weight was measured once a month. The cumulative body weight and fortnightly and daily body weight gains were greatest in the goats reared on fodder + rice polish + maize flour + probiotics + enzymes (T4), at 15540.00 g, 7690.00 g, and 91.55 g, respectively. The mean daily feed consumption was highest in goats fed fodder + maize flour + probiotics + enzymes (T3), at 567.54 g. The feed conversion ratio of 5.48 was highest in goats fed fodder along with rice polish and maize flour supplemented with probiotics and enzymes. The greatest body length (4.25 inches), wither height (3.250 inches) and heart girth (4.750 inches) were detected in goats fed fodder along with rice polish and maize flour supplemented with probiotics and enzymes. The highest (1: 3.31) benefit cost ratio was obtained from goats reared on fodder + rice polish + maize flour + probiotics + enzymes (T4), and the lowest (1: 2.00) benefit cost ratio was obtained from those reared on fodder only (T1). The results obtained from the feeding trial revealed that crossbred goat kids (Khari × Jamunapari) reared on fodder supplemented with rice polish and maize flour supplemented with enzymes and probiotics improved live weight, daily live weight gain, feed efficiency, net profit over the control, and the cost ratio.